Analisis Menurunnya Kualitas Air Sumur Akibat Pembuangan Limbah Rumah Tangga Yang Tidak Tepat - Elvi Sunarsih; Abelia Anggraini; Amri Anwar Sanusi; Amrina Rosyada; Anggun Wafiq Nurhaliza; Junisa Anggraini; Rizka Eka Putri (Universitas PGRI Palembang, 2023)
Water is a basic need that must be fulfilled in everyday human life so that the quality of clean water must be used as a need for bathing, drinking, cooking, and so on. Apart from that, we want to reveal things that can contaminate this basic human need by conducting a literature review. The purpose of this literature analysis is to find out how many residents in this research area still dispose of household waste in an inappropriate manner or inaccurately in the placement of liquid and solid waste materials which will later have an impact on the surrounding environment. The research was conducted using a literature review. Construction of wells must comply with safe and good characteristics so that the quality of well water does not threaten human health. The standard distance of the well from the source of pollution that is generally used is 10 meters.